Stereoselective synthesis of (+)-boronolide - Naidu, SV; Gupta, P; Kumar, P (Tetrahedron Letters, 2005)
An efficient enantio- and stereocontrolled total synthesis of (+)-boronolide from valeralclehyde is described. The key steps include a Sharpless asymmetric dihydroxylation, a chelation controlled Grignard reaction followed by Sharpless asymmetric epoxidation and a ring closing metathesis. (C) 2005 Elsevier Ltd. All rights reserved.